Analysis of Discourse Structure in Higher Education Hymns (Studies at State Universities in East Java) - Parto Parto; Yulianto Bambang; Kisyani Kisyani (BIRCU, 2020)
The purpose of this research is to describe and find the discourse structure of college hymns through macro structure, superstructure, and micro structure. This research was conducted using a qualitative descriptive approach. Source of hymn data for seven state universities in East Java. The selection of seven state universities in East Java was based on the reason that the ways in which higher education hymns were created were similar so that the results of this study could become a reference in the meaning of university hymns in general. Based on the results of data analysis, it can be concluded that (1) the hymn of state universities in East Java has similarities in its macro structure, namely the theme of praise or worship, (2) the superstructure or schematic structure of the hymn in public universities in East Java begins with the naming or title of the hymn which is similar, namely beginning with the word hymn and followed by the name of the institution; In general, the form of a hymn is made in stanzas like a song or poetry (3) semantically a college hymn generally leads the audience to an opinion that the university is praiseworthy and proud, (4) based on the cohesion of the hymn of state universities in East Java generally the hymn descriptions are related to the title, either the overall description or the description of the sections or the comparisons, even each line in the hymn of public universities in East Java refers to or is directed at the institution whose name is mentioned in the title; active and passive sentences, (5) diction in the hymn text of state universities in East Java, like songs in general, are very concerned with the harmony of the sound of language or emphasizing rhyme and poetry, especially diction at the end of the line (6) hymns of public universities in East Java tends to use simple language, but from the analysis results it is found that several styles of language.